Factors Influencing the Formation, Continuation, and Dissolution of Marital Relationships in Iran in 2022: A Qualitative Analysis - Taghadossi, Masood; Farahani, Mohammad Naghi; Manteghi, Morteza (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The aim of this study was to identify the factors influencing the formation, continuation, and dissolution of Iranian marriages in the year 2022.Methods: This research utilized a qualitative method based on the Strauss and Corbin approach. A purposive selection of 10 experts, either faculty members or influential figures in decision-making centers for marriage and family affairs, were deeply interviewed. The data obtained from these experts provided a semi-structured questionnaire for interviews with 36 individuals, divided into three groups: formation, continuation, and dissolution of marriages. After each interview, data were coded and categorized according to the Strauss and Corbin method.Findings: In total, 2950 primary codes, 462 secondary codes, 97 concepts, 27 subcategories, and 9 main categories were identified, including external couple factors affecting formation, continuation, and dissolution; internal couple factors affecting formation, continuation, and dissolution; and individual factors affecting formation, continuation, and dissolution.Conclusion: The results indicated that the formation of marriage is influenced more by external couple factors than by any other factors. Although the continuation and dissolution of marriage are influenced by the nature of their formation, individual factors become important in these stages. It can be inferred that focusing on external couple factors before individual and internal couple factors in pre-marital counseling, and prioritizing individual factors in couple therapy and divorce counseling, may be more effective. It is recommended that the results of this study be used in planning, research, and therapeutic interventions in the field of marriage